A novel framework for seismic risk assessment of structures. (31st August 2022) - Giannini, Renato; Paolacci, Fabrizio; Phan, Hoang Nam; Corritore, Daniele; Quinci, Gianluca
Abstract: Seismic risk assessment of new and existing structures has a long history, which is based on the development of specific methods for seismic hazard and vulnerability analyses. Performance‐based earthquake engineering is the natural evolution and integration of all these aspects that is nowadays implemented in several precodes. However, some critical aspects are not yet completely clarified. As a matter of fact, the vulnerability analysis suffers the so‐called record‐to‐record variability, which is usually controlled through different parameters used as seismic intensity measures (IMs), whose significance is still under discussion. Moreover, this variability represents an additional source of uncertainty, which is added to the dispersion derived from the ground motion prediction equation (GMPE), leading to an overconservatism. For these reasons, the present paper aims to propose a novel framework for the seismic risk assessment of structures, which is found on the idea to control the response variability in evaluating seismic hazard curves without taking into account the randomness (ε) of the GMPE, which instead is transferred to fragility curves. These latter are built by using groups of accelerograms, whose median and 84% fractile spectra fit well, for different return periods, the uniform hazard spectra for ε= 0 and 1, respectively. For this purpose, a new search algorithm for selecting natural records is formulated. The proposed method offers considerable advantages as it is no longer necessary to refer to a specific IM, and allows to select pairs of spectrum‐compatible natural records, which is enable to solve the problem of the seismic assessment of three‐dimensional structures. The procedure is then applied to assess seismic risk of a typical reinforced concrete frame, whose results demonstrate the robustness of the method and the practical independence from the record set used.